O15.3 Cost-effectiveness of antimicrobial resistance point-of-care testing for optimising the treatment of gonorrhoea. (8th July 2017) - Harding-Esch, Emma; Huntington, Susie E; Harvey, Mike; Broad, Claire E; Adams, Elisabeth J; Sadiq, S Tariq
Abstract : Introduction: Antimicrobial resistance (AMR) threatens successful Neisseria gonorrhoeae (NG) treatment and WHO recommends specific NG treatments be used only if ≤5% circulating strains are resistant to them. Ceftriaxone plus azithromycin dual therapy, currently recommended, has few practical alternatives should ceftriaxone resistance become widespread, and azithromycin use is undermined also by AMR emergence. Point-of-care tests for AMR (POCTR) at NG diagnosis may enable a significant proportion of NG infections to be successfully treated using previously abandoned regimens, thereby sparing ceftriaxone use. We assess cost-effectiveness of British standard of care (SC) vs hypothetically accurate POCTR strategies used to either optimise dual therapy or allow monotherapy in patients diagnosed with NG. Methods: A decision tree was constructed to simulate a hypothetical cohort of 38, 870 NG-diagnosed GUM clinic attendees, representing 2015 annual numbers in England. Costs of AMR testing, NG treatment and return attendances were considered for SC and dual therapy optimisation strategies: A) POCTR for ciprofloxacin only; B) POCTR for azithromycin followed by POCTR for ciprofloxacin; C) POCTR for ciprofloxacin followed by POCTR for azithromycin; and monotherapy POCTR strategies for: D) azithromycin; E) ciprofloxacin; F) amoxicillin/probenecid. Results: Total costs for all POCTR strategies were more expensive than SC. Strategy B (where azithromycin-ceftriaxone remains largely first-line) was most cost-effective for avoiding sub-optimal treatments, costing £4532 per optimal treatment gained. Strategy D was most cost-effective for ceftriaxone use avoidance (98% decrease [713 vs 38 870] compared to SC), costing £16.27 per ceftriaxone-sparing treatment gained, but resulting in 7 treatment failures ( vs 0 in SC) due to false AMR POCTR results. Conclusion: Specific POCTR strategies enable optimal treatment and ceftriaxone use avoidance, thus promoting antibiotic stewardship. The public health impact of sparing ceftriaxone whilst increasing treatment failures must be investigated.